Between Praise and Prohibition: How the Ming State Coped with Extreme Filiality. (2nd January 2016) - Zong, Yun
Abstract : Stimulated by honors conferred by the government during the Tang and Song periods, filial piety, by the beginning of the Ming, was being taken to extremes. In 1394 Ming Taizu (Zhu Yuanzhang) responded by banning honors for extreme filial demonstrations. Along with this prohibition, however, his decree confirmed the legitimacy of such actions, demonstrating a strategy of safeguarding the fundamental interests of the throne by any means possible. The flexibility of the decree was given full play by Taizu's successors, who all drew on filial piety as a ruling technique. Even when not issuing official honors for extreme filiality, Ming emperors regularly might award letters to encourage it. The way in which Ming officials coped with the contradictory policy underlies the proclivity of Ming commoners for filial behavior that stretched the boundaries of what was accepted.